Prediagnostic Appearance of Thrombospondin Type-1 Domain 7A Autoantibodies in Membranous Nephropathy - Burbelo, Peter D.; Olson, Stephen W.; Keller, Jason M.; Joshi, Megha; Schwartz, Daniella M.; Chuang, Yung-Jen; Lambeau, Gérard; Beck, Laurence H.; Waldman, Meryl (Kidney360, 2023)
Key PointsThe entire extracellular domain of thrombospondin type-1 domain 7A (THSD7A) in the luciferase immunoprecipitation system immunoassay was required to detect autoantibodies with high sensitivity in membranous nephropathy (MN).In THSD7A-seropositive MN patients, changes in antibody levels precede changes in clinical status.Seropositive THSD7A antibodies were detected in some patients with MN considered to be secondary to autoimmunity or cancer.BackgroundPathogenic autoantibodies against thrombospondin type-1 domain 7A (THSD7A) are present in approximately 3% of patients with membranous nephropathy (MN). Compared with PLA2R antibodies, less is known about THSD7A autoantibodies (ABs) because of the relative rarity and the lack of a commercially available quantitative immunoassay.MethodsIn this study, we describe the development and validation of a highly quantitative luciferase immunoprecipitation system (LIPS) assay for detecting THSD7A ABs and used it to study dominant THSD7A epitopes, disease associations, and monitoring disease activity. The Department of Defense Serum Repository (DODSR) was then used to analyze THSD7A AB in 371 longitudinal serum samples collected before clinical diagnosis of MN from 110 PLA2R-negative MN subjects.ResultsLIPS analysis demonstrated that a near full-length THSD7A (amino acids 1-1656) detected robust autoantibody levels in all known seropositive MN patients with 100% sensitivity and specificity compared with ELISA and/or Western blotting. Most of the THSD7A-seropositive subjects in our pilot cohort had evidence of coexisting autoimmunity or cancer. Moreover, three THSD7A-seropositive patients undergoing immunosuppressive therapy showed longitudinal autoantibody levels that tracked clinical status. Additional epitope analysis of two smaller protein THSD7A fragments spanning amino acids 1-416 and 1-671 demonstrated lower sensitivity of 32% and 44%, respectively. In the DODSR cohort, THSD7A seropositivity was detected in 4.5% of PLA2R-negative MN patients. In one primary and in one secondary MN-associated with cancer, THSD7A ABs were detectable <1 month before biopsy-proven diagnosis. In addition, three patients with lupus membranous nephropathy had detectable THSD7A ABs years before hypoalbuminemia and biopsy-proven diagnosis.ConclusionsAlthough further studies are needed to explore the significance of THSD7A ABs in lupus membranous nephropathy, this study describes a novel, highly sensitive LIPS immunoassay for detecting THSD7A ABs and adds to the existing literature on THSD7A-associated MN.Clinical Trial registry name and registration number:NCT00977977; registration date: September 16, 2009.